Penerapan Media Audio Visual dalam Meningkatkan Hasil Pembelajaran Sejarah Kebudayaan Islam Pada Siswa SD IT Ibnu Qoyyim Pekanbaru - Yoanda Eka Putera; Salman Salman; Sakban Sakban; Deprizon Deprizon (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
The low learning outcomes of students in class 5 Islamic cultural history learning is the main problem faced by students, students often experience feelings of boredom, boredom, and permission from the class and have difficulty understanding Ski learning which is taught conventionally. The aim of the research is to improve student learning outcomes by using the application of audio-visual media in learning the history of Islamic culture. This research method includes Classroom Action Research (PTK) which was carried out in 2 cycles. Each cycle consists of four stages, namely Design, Implementation, Observation, Reflection. The research results obtained were (1) Teacher activity in cycle I before using audio-visual media was 83.92%. In cycle II after using audio-visual media 92.85%, (2) Student activity before using audio-visual media 67% and after using audio-visual media 90%. This shows that the results of student learning on the Fathu Mecca and the Death of the Prophet Muhammad, using Audio Visual Media in Learning the History of Islamic Culture show very positive results.